Polypropylene composition as well as preparation method and application thereof
By adding styrene-based elastomers, compatibilizers, glass fibers and nucleating agents to the polypropylene material, the problems of low light transmittance and high shrinkage during the welding process are solved, and its tensile strength, welding strength and light transmittance are significantly improved, which is suitable for the manufacturing of automotive parts.
Patent Information
- Application Number
- CN202510106678.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-18
AI Technical Summary
The existing polypropylene materials have low light transmittance during welding, which limits their application in the field of automotive parts, and at the same time, their high shrinkage rate leads to product surface defects.
A polypropylene composition is used, including polypropylene resin, styrene-based elastomer, compatibilizer, glass fiber and nucleating agent, through the combined action of these components, the tensile strength, welding strength and light transmittance of the material are improved.
The tensile strength, welding strength and light transmittance of the polypropylene composition are significantly improved, and the welding band is expanded, making it more suitable for the manufacturing of automotive parts, especially the preparation of automobile bumpers.
Smart Images

Figure BDA0005255621380000081 
Figure BDA0005255621380000091 
Figure BDA0005255621380000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polypropylene composition and a preparation method and application thereof. Background Art
[0002] In recent years, as the demand for lightweight automobiles has become increasingly strong, lightweight design and manufacturing of automobile parts have also become important technical indicators for automobile parts production. Polypropylene has comprehensive advantages that other plastics cannot achieve, such as low density, abundant raw material sources, low cost, and good weather resistance. It has been one of the fastest growing plastic varieties in recent years. However, due to the high shrinkage rate of PP materials, thin-wall design will bring about defects such as surface shrinkage, ejector marks, and stress marks in the subsequent development process, which has become a great pain point in the product development process. Especially for the high requirements for the appearance of automotive exterior parts, it is imperative to optimize and improve the product connection method.
[0003] Laser welding has many advantages, such as extremely fast heating and cooling speeds, which greatly reduces the thermal stress and vibration stress of plastic products; simple control, non-contact processing, strong adaptability, and strong operability for complex structures or small welds; the equipment is easy to maintain, easy to operate, and supports long-term use, and there is no pollution during the welding process. It is a very environmentally friendly welding technology. To achieve laser welding, there are certain requirements for the transmittance of the material's light-transmitting layer. The higher the transmittance, the greater the laser transmittance, the more energy is transferred to the light-absorbing layer, and the better the laser welding effect. However, due to its semi-crystalline characteristics, the low transmittance and glossiness of ordinary PP materials limit their application in the field of welding products.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polypropylene composition and a preparation method and application thereof, which effectively improve the tensile strength, laser welding strength and light transmittance of the polypropylene composition.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A polypropylene composition comprises the following components in parts by weight: 42 to 82 parts of a polypropylene resin, 4 to 42 parts of a styrene elastomer, 4 to 21 parts of a compatibilizer, 4 to 21 parts of glass fibers, and 0.18 to 2.1 parts of a nucleating agent;
[0008] The nucleating agent includes at least one of an α-crystal nucleating agent and a β-crystal nucleating agent.
[0009] The present invention creatively combines the above raw materials, takes polypropylene resin as the matrix, and effectively improves the tensile strength, welding tensile strength and light transmittance of the polypropylene composition under the joint action of styrene elastomer, compatibilizer, glass fiber and nucleating agent, thereby having a wider welding band. The polypropylene composition is very suitable for preparing automobile parts, especially for preparing automobile bumpers.
[0010] In the polypropylene resin matrix system of the present invention, a styrene elastomer is added, and the styrene elastomer can refine the grains, increase the amorphous region inside the polypropylene, reduce the scattering of light, improve the light transmittance, improve the fluidity of the melt, and help improve the processing performance of the system; the styrene elastomer and the compatibilizer jointly improve the compatibility of the system, improve the dispersibility of the glass fiber in the system, and the glass fiber plays a skeleton role in the system, effectively improving the strength of the system; the addition of the nucleating agent effectively improves the crystallization effect, refines the spherulites, and enhances the light transmittance.
[0011] Wherein, the amount of the polypropylene resin is 42 to 82 parts, for example, it can be 42 parts, 45 parts, 48 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 82 parts or a range consisting of any two of the values.
[0012] Preferably, the amount of the polypropylene resin is 45 to 80 parts.
[0013] Among them, the amount of the styrene elastomer is 4 to 42 parts, for example, it can be 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 42 parts or a range consisting of any two of the values.
[0014] Preferably, the amount of the styrene elastomer is 5 to 40 parts.
[0015] The amount of the compatibilizer is 4 to 21 parts, for example, 4 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 21 parts or a range consisting of any two of these values.
[0016] Preferably, the amount of the compatibilizer is 5 to 20 parts.
[0017] Preferably, the amount of the glass fiber is 4 to 21 parts, for example, 4 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 21 parts or a range consisting of any two of these values.
[0018] Preferably, the amount of the glass fiber is 5 to 20 parts.
[0019] Preferably, the nucleating agent is an organic nucleating agent, and the amount of the nucleating agent is 0.18 to 2.1 parts, for example, it can be 0.18 parts, 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.1 parts or a range consisting of any two of these values.
[0020] Preferably, the amount of the nucleating agent is 0.2 to 2 parts.
[0021] Preferably, the polypropylene composition comprises the following components in parts by weight: 45 to 80 parts of polypropylene resin, 5 to 40 parts of styrene elastomer, 5 to 20 parts of compatibilizer, 5 to 20 parts of glass fiber, and 0.2 to 2 parts of nucleating agent.
[0022] Preferably, the polypropylene composition comprises the following components in parts by weight: 50 to 65 parts of polypropylene resin, 20 to 30 parts of styrene elastomer, 10 to 15 parts of compatibilizer, 10 to 15 parts of glass fiber, and 1 to 1.5 parts of nucleating agent. In particular, when the amount of each raw material is within this range, the compatibility is better, and under the joint action of each component, the tensile strength, welding tensile strength and light transmittance are further improved.
[0023] Wherein, in the polypropylene composition of the present invention, the weight percentage of the polypropylene resin is not less than 40%.
[0024] Preferably, in the polypropylene composition of the present invention, the weight percentage of the polypropylene resin is 40-73%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 72%, 73% or a range consisting of any two of these values.
[0025] Preferably, the polypropylene resin is a homopolymer polypropylene resin.
[0026] Preferably, the polypropylene resin has a melt flow rate of 3 to 150 g / 10 min at 230 ° C / 2.16 kg according to the ISO1133-2011 method, for example, it can be 3 g / 10 min, 5 g / 10 min, 8 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 100 g / 10 min, 110 g / 10 min, 120 g / 10 min, 130 g / 10 min, 140 g / 10 min, 150 g / 10 min or a range consisting of any two of the values.
[0027] Preferably, the nucleating agent includes an α-crystal nucleating agent and a β-crystal nucleating agent, and the mass ratio of the α-crystal nucleating agent to the β-crystal nucleating agent is (0.5-3):1. In particular, a combination nucleating agent of an α-crystal nucleating agent and a β-crystal nucleating agent in this mass ratio is used, and α-crystal and β-crystal are simultaneously formed during the crystallization process to achieve double crystallization, which can further refine the grains, promote the formation of more amorphous regions, and synergistically improve the tensile strength, welding tensile strength and light transmittance.
[0028] Preferably, the α-crystal nucleating agent includes at least one of an organic phosphate α-crystal nucleating agent, an organic carboxylate α-crystal nucleating agent, and a sorbitol α-crystal nucleating agent.
[0029] Preferably, the β-crystal nucleating agent includes at least one of an aromatic amide β-crystal nucleating agent and an organic carboxylic acid β-nucleating agent.
[0030] Preferably, the compatibilizer includes at least one of maleic anhydride grafted POE and maleic anhydride grafted polypropylene.
[0031] Preferably, the compatibilizer is maleic anhydride grafted POE, and the grafting rate of maleic anhydride in the maleic anhydride grafted POE is ≥0.3%. In particular, the use of maleic anhydride grafted POE can further improve the compatibility, improve the fluidity of the system, improve the processing performance, reduce phase separation and light scattering, thereby further improving the tensile strength, welding tensile strength and transmittance.
[0032] Preferably, the compatibilizer is maleic anhydride grafted POE, and the grafting rate of maleic anhydride in the maleic anhydride grafted POE is 0.3-1%, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two values therein.
[0033] The maleic anhydride grafting rate can be determined by infrared spectroscopy: a sample of fixed thickness is tested by Fourier transform infrared spectrometer to obtain characteristic absorption peaks of infrared spectrum, and the maleic anhydride grafting rate can be calculated by comparing the ratio of carbonyl and methylene absorption intensities.
[0034] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted POE is 0.8-1%.
[0035] The POE in the maleic anhydride grafted POE is a thermoplastic elastomer obtained by in-situ polymerization of ethylene and α-olefin using a metallocene catalyst, wherein the α-olefin includes at least one of α-olefins having 4 to 8 carbon atoms.
[0036] Preferably, the α-olefin includes at least one of 1-butene, 1-hexene and 1-octene.
[0037] Furthermore, the POE is preferably a thermoplastic elastomer obtained by in-situ polymerization of ethylene and 1-octene using a metallocene catalyst.
[0038] Preferably, the maleic anhydride grafted POE has a melt mass flow rate of 0.1 to 2 g / 10 min at 190° C. / 2.16 kg according to the method of ISO1133-2011.
[0039] Preferably, the styrene content in the styrene elastomer is 13-41wt%, for example, it can be 13wt%, 15wt%, 16wt%, 18wt%, 20wt%, 25wt%, 30wt%, 32wt%, 35wt%, 37wt%, 40wt%, 41wt%.
[0040] Preferably, the styrene content in the styrene elastomer is 18-30 wt%.
[0041] Preferably, the method for testing styrene in the styrene elastomer is: cut the sample into pieces, take 0.02-0.05g of the sample, dissolve it with a deuterated reagent, perform nuclear magnetic resonance, and then quantify it according to the nuclear magnetic peak area normalization method.
[0042] Preferably, the styrene-based elastomer includes at least one of hydrogenated styrene-butadiene-styrene terblock copolymer (SEBS for short) and styrene-butadiene-styrene terblock copolymer (SBS for short).
[0043] Preferably, the melt flow rate of the styrene elastomer at 230°C / 2.16kg is 0.1-40g / 10min, for example, it can be 0.1g / 10min, 0.5g / 10min, 1g / 10min, 2g / 10min, 4g / 10min, 8g / 10min, 10g / 10min, 20g / 10min, 30g / 10min, 40g / 10min or a range consisting of any two of the values, and the test standard is ISO1133-2011.
[0044] Preferably, the average monofilament diameter of the glass fiber is 9-14 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or a range consisting of any two values therein.
[0045] Preferably, the average monofilament diameter of the glass fiber is 10-14 μm.
[0046] Preferably, the average monofilament length of the glass fiber is 2-10 mm, for example, 2 mm, 3 mm, 5 mm, 8 mm, 10 mm or a range consisting of any two values therein.
[0047] In the present invention, the average monofilament diameter of the glass fiber is tested by a microscope method: 100 glass fiber samples are placed under a microscope for observation, the diameters of all glass fibers in the sample are calculated, and the average value is calculated to obtain the average monofilament diameter of the glass fiber.
[0048] Preferably, 0.1 to 1 parts by mass of an antioxidant is also included.
[0049] Preferably, the antioxidant includes but is not limited to at least one of antioxidant 1098, antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0050] Preferably, the polypropylene composition of the present invention may further include at least one of mineral powder, lubricant, colorant, weathering agent, antistatic agent, flame retardant and ultraviolet light absorber.
[0051] The polypropylene composition of the present invention may include mineral powder. Suitable mineral powders include, but are not limited to, calcium carbonate, mica, kaolin, magnesium hydroxide, boehmite, and combinations thereof.
[0052] The polypropylene composition of the present invention may include a colorant. Suitable colorants include, but are not limited to, carbon black, titanium dioxide, zinc sulfide, red iron oxide, titanium yellow, and combinations thereof.
[0053] The polypropylene composition of the present invention may include a lubricant. Suitable lubricants include, but are not limited to, polyethylene wax, fatty acid esters, hyperbranched amides, and combinations thereof.
[0054] The polypropylene composition of the present invention may include a weathering agent, and suitable weathering agents include but are not limited to hindered amine light stabilizers and combinations thereof.
[0055] The polypropylene composition of the present invention may include an antistatic agent. Suitable antistatic agents include, but are not limited to, zinc oxide, manganese dioxide, chromium trioxide, and combinations thereof.
[0056] The polypropylene composition of the present invention may include a flame retardant, and suitable flame retardants include, but are not limited to, brominated polymers (e.g., brominated polystyrene), metal dialkyl phosphites (e.g., tris(diethylphosphite)aluminum), metal hydroxides (e.g., magnesium hydroxide), aromatic phosphates (e.g., resorcinol di(diphenyl phosphate) ester and bisphenol A di(diphenyl phosphate) ester), and combinations thereof.
[0057] The polypropylene composition of the present invention may include a UV absorber. Suitable UV absorbers include, but are not limited to, hydroxybenzophenones, benzotriazoles, hydroxybenzotriazines, cyanoacrylates, nanoscale inorganic materials (eg, titanium oxide, cerium oxide, and zinc oxide), and combinations thereof.
[0058] The present invention also provides a method for preparing a polypropylene composition, comprising the following steps:
[0059] According to the ratio, the components except glass fiber are mixed uniformly, put into a twin-screw extruder for melt mixing, the glass fiber is side-fed, and extruded into granules to obtain a polypropylene composition.
[0060] The invention also provides an application of the polypropylene composition in the preparation of automobile parts.
[0061] The polypropylene composition of the present invention has excellent tensile strength, welding tensile strength and light transmittance, and is very suitable for preparing automobile parts, especially for preparing automobile bumpers.
[0062] The present invention also provides a bumper, which is prepared by using the polypropylene composition described above.
[0063] The beneficial effects of the present invention are as follows: the present invention uses polypropylene resin as a matrix, and under the joint action of a styrene elastomer, a compatibilizer, glass fiber, and a nucleating agent, effectively improves the tensile strength, welding tensile strength, and light transmittance of the polypropylene composition, thereby having a wider welding band. The polypropylene composition is very suitable for preparing automotive parts, especially for preparing automotive bumpers. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0065] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0066] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0067] The raw materials used in the embodiments and comparative examples are described as follows:
[0068] Polypropylene resin-1: Shaoxing Sanjin, brand PP Y26SY.
[0069] Polypropylene resin-2: Sinopec, brand PPH-T03.
[0070] Polypropylene resin-3: Sinopec, brand MN150.
[0071] Styrene elastomer-1: SEBS, styrene content 30 wt%, Kraton Polymer Trading, brand G1652.
[0072] Styrene Elastomer-2: SEBS, styrene content 18 wt%, Kraton Polymers Trading, brand G1643M.
[0073] Styrene Elastomer-3: SEBS, styrene content 13 wt%, Kraton Polymers Trading, brand G1657.
[0074] Styrene Elastomer-4: SEBS, styrene content 41 wt%, Kraton Polymers Trading, brand RP6936.
[0075] Styrene elastomer-5: SBS, styrene content is 30wt%, Baling Petrochemical, brand YH-791.
[0076] POE elastomer: Dow Chemical, brand POE8200.
[0077] MAH-g-POE-1: Maleic anhydride grafted POE, maleic anhydride grafting rate 1%, Bochen polymer, brand PC-28.
[0078] MAH-g-POE-2: maleic anhydride grafted POE, maleic anhydride grafting rate is 0.8%, Coase Chemical Co., Ltd., brand W1.
[0079] MAH-g-POE-3: maleic anhydride grafted POE, maleic anhydride grafting rate is 0.3%, Shenyang Ketong Company, brand KT-915B.
[0080] MAH-g-PP: maleic anhydride grafted polypropylene, maleic anhydride grafting rate is 1%, Jiayirong Company, brand CMG-5701.
[0081] Glass fiber-1: the average monofilament diameter is 13.5 μm, purchased from Jushi Company, brand number ECS13-03-508A.
[0082] Glass fiber-2: the average monofilament diameter is 10 μm, purchased from Jushi Company, brand number ECS10-03-584.
[0083] Nucleating agent-1: organic carboxylate α-crystalline nucleating agent, Milliken, brand HPN-68L.
[0084] Nucleating agent-2: organic phosphate α-crystal nucleating agent, bis[2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate]hydroxyaluminum salt), Shanxi Chemical Industry Research Institute, brand TMP-5.
[0085] Nucleating agent-3: sorbitol-based α-crystal nucleating agent, dibenzylidene sorbitol, Guangzhou Chenghe Technology Co., Ltd.; brand NA-98.
[0086] Nucleating agent-4: Aromatic amide β-crystal nucleating agent, n,n′-dicyclohexyl-2,6-naphthalene dicarboxamide, commercially available.
[0087] Nucleating agent-5: organic carboxylic acid β-crystal nucleating agent, calcium tetrahydrophthalate, Guangzhou Chenghe Technology Co., Ltd.; brand NAB-82.
[0088] Nucleating agent-6: Inorganic nucleating agent, nano-alumina, Hebei Zhuyan Alloy Materials Co., Ltd.
[0089] Antioxidant: A mixture of antioxidant 1010 and antioxidant 168, with a mass ratio of 1:1.
[0090] Examples 1 to 23, Comparative Examples 1 to 4
[0091] The formulations of the polypropylene compositions of Examples 1 to 23 and Comparative Examples 1 to 4 are shown in Table 1 and Table 2 (all in the tables are parts by weight).
[0092] The preparation methods of the polypropylene compositions of Examples 1 to 23 and Comparative Examples 1 to 4 all include the following steps:
[0093] According to the ratio, the components except the glass fiber are mixed evenly, put into a twin-screw extruder (length-to-diameter ratio of 40:1) for melt mixing, and the glass fiber is fed from the side. The processing temperatures (from the feeding port to the die head) are: 100°C, 180°C, 180°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, and the screw speed is 500rpm. Extrusion granulation is carried out to obtain a polypropylene composition.
[0094] Table 1
[0095]
[0096] Table 2
[0097]
[0098]
[0099] Performance Testing
[0100] Tensile Strength: Tested according to ISO 527-2-2012, 1A specimen, 10mm / min.
[0101] Light transmittance: According to GB / T 2410-2008, 2mm.
[0102] Welding tensile strength: tested in accordance with ISO 527-2-2012, welding specimen size 100*10*2mm, 10mm / min.
[0103] The welding specimens were prepared as follows: the composition obtained above was placed in an oven at 120° C. for 4 hours and two specimens (divided into laser-transmitting specimens and laser-absorbing specimens, wherein the laser-absorbing specimens were additionally added with laser-absorbing color powder in the formula, the addition amount of laser-absorbing color powder was 1500 ppm, and the laser-absorbing color powder was Raven M carbon black) with a size of 100*10*2 mm were respectively made using an injection molding machine, the barrel temperature was 280° C., and the mold temperature was 120° C. The laser-transmitting specimens and the laser-absorbing specimens were overlapped, and the laser-transmitting specimens were placed toward the laser focusing window for laser welding.
[0104] The laser welding system (Han's Laser, model WFD120 W-PCTS333SP) used for laser welding was diode laser (wavelength 915 nm), laser radius 200 μm, welding power 20 W, welding speed 20 mm / s, welding length 130 mm × 3 (in order to reduce the error, three independent welds without overlap were performed, each weld was parallel and spaced 6 mm apart), and the pressure of the pneumatic holding device was 0.5 MPa. The average value of the welding tensile strength under the three parallel welding conditions was recorded.
[0105] Table 3
[0106]
[0107]
[0108] It can be seen from Table 3 that the polypropylene composition of the present invention has excellent tensile strength, welding tensile strength and light transmittance, and is very suitable for preparing automobile parts, especially for preparing automobile bumpers. The tensile strength of the polypropylene composition of the present invention is ≥26.8MPa, the light transmittance is ≥64%, and the welding tensile strength is ≥16MPa.
[0109] By comparing Example 1 with Comparative Examples 1 to 4, it can be seen that the present invention uses polypropylene resin as a matrix, and under the joint action of styrene elastomer, compatibilizer, glass fiber and nucleating agent, the tensile strength, welding tensile strength and light transmittance of the polypropylene composition are effectively improved.
[0110] By comparing Examples 2 to 3 with Examples 1 to 4, it can be seen that by controlling the amount of each raw material to: 50 to 65 parts of polypropylene resin, 20 to 30 parts of styrene elastomer, 10 to 15 parts of compatibilizer, 10 to 15 parts of glass fiber, 1 to 1.5 parts of nucleating agent, especially when the amount of each raw material is within this range, the compatibility is better, and under the joint action of each component, the tensile strength, welding tensile strength and light transmittance are further improved.
[0111] Comparative Examples 3, 7 to 10 show that the present invention further improves the tensile strength, welding tensile strength and light transmittance by controlling the styrene content of the styrene elastomer to 18 to 30 wt %.
[0112] By comparing Examples 3 and 11 to 13, it can be seen that the present invention further improves the tensile strength, welding tensile strength and light transmittance by using maleic anhydride grafted POE with a grafting rate of maleic anhydride ≥ 0.8 as a compatibilizer.
[0113] By comparing Examples 3 and 14 to 22, it can be seen that the present invention further improves the tensile strength, welding tensile strength and light transmittance by using an α-crystal nucleating agent and a β-crystal nucleating agent in a mass ratio of (0.5 to 3):1.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composition, characterized in that The invention comprises the following components in parts by weight: 42 to 82 parts of polypropylene resin, 4 to 42 parts of styrene elastomer, 4 to 21 parts of compatibilizer, 4 to 21 parts of glass fiber, and 0.18 to 2.1 parts of nucleating agent; The nucleating agent includes at least one of an α-crystal nucleating agent and a β-crystal nucleating agent.
2. The polypropylene composition according to claim 1, characterized in that The nucleating agent includes an α-crystal nucleating agent and a β-crystal nucleating agent, and the mass ratio of the α-crystal nucleating agent to the β-crystal nucleating agent is (0.5-3):
1.
3. The polypropylene composition according to claim 1, characterized in that The α-crystal nucleating agent includes at least one of an organic phosphate α-crystal nucleating agent, an organic carboxylate α-crystal nucleating agent, and a sorbitol α-crystal nucleating agent; and / or The β-crystal nucleating agent includes at least one of an aromatic amide β-crystal nucleating agent and an organic carboxylic acid β-nucleating agent.
4. The polypropylene composition according to claim 1, characterized in that The compatibilizer includes at least one of maleic anhydride grafted POE and maleic anhydride grafted polypropylene.
5. The polypropylene composition according to claim 4, characterized in that The compatibilizer is maleic anhydride grafted POE, and the grafting rate of maleic anhydride in the maleic anhydride grafted POE is ≥0.3%.
6. The polypropylene composition according to claim 1, characterized in that The styrene content of the styrene elastomer is 13 to 41 wt%; and / or The styrene-based elastomer includes at least one of a hydrogenated styrene-butadiene-styrene terblock copolymer and a styrene-butadiene-styrene terblock copolymer.
7. The polypropylene composition according to claim 1, characterized in that It also includes 0.1 to 1 parts by weight of an antioxidant.
8. The method for preparing the polypropylene composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: According to the ratio, the components except glass fiber are mixed uniformly, put into a twin-screw extruder for melt mixing, the glass fiber is side-fed, and extruded into granules to obtain a polypropylene composition.
9. Use of the polypropylene composition according to any one of claims 1 to 7 in the preparation of automobile parts.
10. A bumper, characterized in that: The polypropylene composition is prepared by using any one of claims 1 to 7.